2012
DOI: 10.1111/j.1445-2197.2012.06256.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled trial comparing dynamic hip screw and screw fixation for undisplaced subcapital hip fractures

Abstract: This study found no difference in outcomes between DHS and cancellous screws in the treatment of subcapital NOFFs in a fit, independent population, but we found a high level of physical decline in previously fit, independently ambulating patients. A large, multicentre trial will be required to differentiate between these two fixation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…19 An updated pooled analysis of reoperation including small trials with our FAITH results (eight trials, 1913 patients) reported a 95% CI that was narrower than our study’s but was still consistent, with no difference between fixation methods (0.91, 0.76–1.08; p=0.27, I 2 =7%). 25–31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 An updated pooled analysis of reoperation including small trials with our FAITH results (eight trials, 1913 patients) reported a 95% CI that was narrower than our study’s but was still consistent, with no difference between fixation methods (0.91, 0.76–1.08; p=0.27, I 2 =7%). 25–31 …”
Section: Discussionmentioning
confidence: 99%
“…The addition of another small trial to a previous meta-analysis results in a significant reduction in the risk of avascular necrosis with sliding hip screws (77 events; relative risk 0.64, 95% CI 0.43–0.97; p=0.04, I 2 =0%). 19,25 …”
Section: Discussionmentioning
confidence: 99%
“…Outcomes after cancellous screw fixation are highly dependent on surgical expertise and the quality of the reduction [6]. Recently we have used two different cannulated compression titanium screws (full threaded versus partial threaded) in the surgical treatment of the adult femoral neck fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques range from internal fixation with multiple cancellous lag screws and sliding hip screws for nondisplaced fractures to multiple cancellous lag screws, sliding hip screws, hemiarthroplasty, and total hip replacement for displaced femoral neck fractures [5][6][7][8]. Options for internal fixation have included a variety of implants [9,10], however most recent reports and textbooks cite parallel multiple cancellous screws as the surgical technique of choice [6][7][8][11][12][13]. Potential advantages of multiple screws over arthroplasty include short duration of surgery, limited surgical trauma and preservation of the native hip joint [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, this was not observed in the present cohort with a previous study similarly demonstrating TAD was independent of femoral neck-shaft angle when using a 135 DHS in 144 hip fractures. 11 The questionnaire revealed that whilst most concepts related to correct lag screw placement were well understood (correct responses in 81% or more for questions [1][2][3][4][5], the common deficiency in knowledge amongst almost half of surgeons related to how to measure TAD (correct responses in 57% for question 6). Correct responses to all questions were independent of surgeon grade and procedural experience apart from question 3 ( Table 5) which demonstrated that surgeons performing more DHS procedures were significantly more likely to correctly identify the ideal lag screw position in the femoral head on the anteroposterior radiographic view.…”
Section: Discussionmentioning
confidence: 99%